THE EFFECT OF REWARD ON ORGANIZATINAL CITIZENSHIP BEHAVIOR (OCB) LECTURERS OF MURIA KUDUS UNIVERSITY (UMK) KUDUS CENTRAL JAVA - Lidinnillah, Farih; Murni, Sylviana; Madhakomala, R. (International Conference on Cultural Studies, 2019)
The objective of this research is to obtain information about the effect of reward on lecturer organizational citizenship behavior of Universitas Muria Kudus (UMK). It was quantitative research with survey method in Universitas Muria Kudus (UMK) Kudus Central Java. The research was conducted to all lecturer of Universitas Muria Kudus (UMK) Kudus Central Java by using a survey method with path analysis applied in testing hypothesis. The number 83 employees as sample was selected by using Slovin formula. The research conlude that there is a direct positive effect of reward on OCB.